Krait envenomation: Strong suspicion and judicious use of anti-snake venom - Lalit Prakash Mali; Sweta Gupta; Deepak Sharma; Mukesh Choudhary (Medical Journal of Dr. D.Y. Patil University, 2015)
Snake bite is common in Rajasthan, particularly in rural areas and in the rainy season. In the majority of cases, we usually get compatible history and clinical sign and/or symptoms. However, sometimes, there may be inconsistent history and fang marks may not be appreciable. Here, we report a case wherein snake passed over the body of the patient, no clear history of biting, without any fang marks and patient presented with neuroparalysis within 2-3 h. After ruling out other possible causes, diagnosis of krait envenomation was kept. Anti snake venom was given along with symptomatic and supportive measures, and the patient was discharged home with no residual neurological deficit.